Teaching children dance - Cone, Theresa Purcell, 1950- 4 0 16; Cone, Stephen Leonard; 5 (Champaign, IL : Human Kinetics, 2005)
A comprehensive guide to introduce children in kindergarten through fifth grade to various dances, and features twenty lessons, and also encourages teachers to incorporate personal style and preferences to the teaching.
Includes bibliographical references (p. 165-171).
Professional;Professional
Keywords: 2 -- 0; 6; Study and teaching.;Study and teaching. -- Dance for children;Dance; 20; 2